2020
DOI: 10.3389/fcell.2020.586651
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Mosaic Cell Labeling Provides Insights Into Pancreatic Islet Morphogenesis

Abstract: Pancreatic islets, discrete microorgans embedded within the exocrine pancreas, contain beta cells which are critical for glucose homeostasis. Loss or dysfunction of beta cells leads to diabetes, a disease with expanding global prevalence, and for which regenerative therapies are actively being pursued. Recent efforts have focused on producing mature beta cells in vitro, but it is increasingly recognized that achieving a faithful three-dimensional islet structure is crucial for generating fully functional beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Although the above studies suggest that the overall mitochondrial network characteristics remained relatively stable during islet assembly, there was generation of new mitochondria in extended cells. We know from previous studies that these cells are highly motile [23,35], and in still images we observed a striking distribution of discrete mitochondrial units at proximal to distal locations in long cellular protrusions (Fig. S6A,B).…”
Section: Directed Mitochondrial Redistribution To Regions Of Dynamic ...supporting
confidence: 59%
See 4 more Smart Citations
“…Although the above studies suggest that the overall mitochondrial network characteristics remained relatively stable during islet assembly, there was generation of new mitochondria in extended cells. We know from previous studies that these cells are highly motile [23,35], and in still images we observed a striking distribution of discrete mitochondrial units at proximal to distal locations in long cellular protrusions (Fig. S6A,B).…”
Section: Directed Mitochondrial Redistribution To Regions Of Dynamic ...supporting
confidence: 59%
“…Although considered ‘ubiquitous’, the EF1a promoter is variably downregulated during development [ 32 , 33 ] and the EF1a:MLS‐EGFP transgenic line appeared not optimal for studies of islet mitochondria. As we previously characterised the robust pancreatic islet expression driven from a 5 kb neurod promoter [ 23 ], we now generated a neurod:mitoGFP transgenic line to label mitochondria in pancreatic islet cells. In the newly established transgenic line, the neurod promoter directed robust expression of a mitochondrial targeted GFP within islet cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations